2023
DOI: 10.3389/fpsyg.2023.1086121
|View full text |Cite
|
Sign up to set email alerts
|

Horticultural therapy for stress reduction: A systematic review and meta-analysis

Abstract: IntroductionHorticultural therapy has been increasingly accepted as a non-pharmacological stress reduction treatment. Previous studies have demonstrated its therapeutic effects, with the effect varying according to the populations, settings, and interventions of horticultural therapy. This study aimed to provide a comprehensive review of the current literature regarding the effectiveness of horticultural therapy in reducing stress.MethodsWe selected databases including PubMed, Cochrane Library, Embase, Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…By observing their own successful experiences, individuals believe in their ability to cope with difficulties and develop problem-solving skills. This confidence and expectation contribute to further enhancing individuals' self-efficacy (Guo et al, 2023;Lu et al, 2023).…”
Section: The Role Of Horticultural Therapy In Self-cognitionmentioning
confidence: 98%
See 2 more Smart Citations
“…By observing their own successful experiences, individuals believe in their ability to cope with difficulties and develop problem-solving skills. This confidence and expectation contribute to further enhancing individuals' self-efficacy (Guo et al, 2023;Lu et al, 2023).…”
Section: The Role Of Horticultural Therapy In Self-cognitionmentioning
confidence: 98%
“…For example, incorporating green plants in office or study spaces has been shown to reduce stress and improve productivity (Li et al, 2022). In addition, horticultural activities cultivate individuals' sense of self-efficacy and mastery through the processes of creativity and problem-solving, thereby building their confidence and resilience (Guo et al, 2023;Lu et al, 2023).…”
Section: The Role Of Horticultural Therapy In Stress Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is a clear gap in research regarding the effects of these interventions on children, indicating the need for empirical studies determining the efficacy of horticultural interventions in aiding children's recovery from psychological and physiological stress. Lu et al (2023) also noted that the stress-relieving effects of horticultural activities are more pronounced in people aged over 60 years.…”
Section: Introductionmentioning
confidence: 95%